The relationship between working environment and office employee’s productivity at Perkeso Kuching, Sarawak / Helmi Sulaiman - Sulaiman, Helmi (2017)
Work environment plays an important role in an organization. Most of the problems faced by employees are related to working environment. Working environment and office design fulfills the employees’ needs and helps to boost their productivity. The main objective of this study was to identify the relationship between working environment and employee’s productivity. It was also to determine the most significant element of working environment that existed in the PERKESO. For this purpose, the researcher selected PERKESO, Kuching. For this research study, a questionnaire was distributed to get the feedback from the respondents. Twenty eight questionnaire was developed which contained 6 section (Demographic, Furniture, Noise, Temperature, Lighting, Productivity and Suggestion). Questionnaires that researcher had distributed are 125 in total, and manages to collected around 119 (96%) from respondents. Results of correlation from this study shows temperature have strongest correlations (r= 0.829**) than noise (r=0.755*), productivity (r=0.373**) and lighting (r=0.356**). The findings also revealed that furniture, noise, temperature, and lighting in the workplace were helpful in developing a working environment that had positive impact on employee’s level of productivity in the organizations